Comparison of the efficacy of diclofenac and indomethacin suppositories in treating perineal pain after episiotomy or laceration: a prospective, randomized, double-blind clinical trial - (:unkn) unknown (SPRINGER HEIDELBERG, 2009)
To compare the results in terms of effectiveness, side effects, and patient satisfaction when diclofenac and indomethacin suppositories were used for the relief of perineal pain after episiotomy or tearing during childbirth. A total of 200 women who had undergone mediolateral episiotomy or suffered lacerations while giving birth vaginally were randomly assigned to receive either rectal diclofenac or indomethacin. Pain ratings were recorded before the administration of drugs and at 1, 3, 6, 9, 12, and 24 h after the first dose on a 10 cm visual analog scale. Side effects and overall opinion on the two treatments were assessed at 24 h. The prophylactic use of diclofenac suppositories reduced perineal pain more than the use of indomethacin suppositories, although the difference was not significant. Overall additional analgesia requirement was correspondingly lower in the diclofenac group. There were no significant differences in overall patient satisfaction between the two groups. Since the two analgesics were rated similarly and gave satisfactory pain relief, diclofenac may be preferred because it is administered in a single dose and requires less nursing time to dispense and is a substantially less costly alternative to the new pain treatment technologies currently in use.
Keywords: Diclofenac; Indomethacin; Episiotomy; Postpartum pain measurement; PATIENT-CONTROLLED ANALGESIA; CESAREAN-SECTION; MORPHINE; RELIEF; SCALE